Pemanfaatan Multimedia pada Pembelajaran PAI-BP Berdiferensiasi dalam Meningkatkan Motivasi Belajar Siswa SMA N 1 Batahan - Anisa Sabila; Khairurrijal; Rohman (Jurnal Pendidikan dan Humaniora Rumbio, 2024)
The aims of this research are 1) to determine differentiated PAI-BP learning at SMA N 1 Batahan, 2) to determine the use of multimedia in differentiated PAI-BP learning at SMA N 1 Batahan, 3) to determine students' learning motivation in differentiated PAI-BP learning at SMA N 1 Batahan. The research used by the author is qualitative research. Qualitative research is a review of various studies and a collection of various types of empirical material, such as case studies, personal experiences. Data collection techniques use observation, interviews and documentation. The data analysis techniques in this research are data reduction, data presentation and drawing conclusions. The results of this research show that differentiated PAI-BP learning at SMA N 1 Batahan includes four aspects in accordance with the rules in differentiated learning, namely a) content, this aspect contains the material that will be taught by the PAI-BP teacher, the material taught by the PAI teacher -BP is analyzing QS. Ali Imran verses 190-191. b) process, determining different student interests. Each student has a different learning system. There is a mind map group, there is an audio-visual group. c) product, which is the result of learning from each group. The audio-video group is assigned to display clear video and sound, d) learning environment, as a teacher of course try to create a pleasant learning environment. In class Utilization of multimedia in differentiated PAI-BP learning at SMA N 1 Batahan by using power point, Canva application and projector.